The Influence of Self-Confidence on Public Speaking Skills of Students of the Office Administration Education Study Program - Asriani Asriani; Haedar Akib; Risma Niswaty (Asha Publishing, 2025)
Academically and professionally, the ability to speak in front of an audience is crucial. Strong public speaking skills are essential for students enrolled in the Office Administration Education Study Program. Concerns such as fear of public speaking and ways to overcome them will be thoroughly investigated in this study. Better understanding these barriers and developing ways to overcome them will undoubtedly enhance students' educational experiences. This study will provide students with a better understanding of their needs, interests, and experiences. This can be useful in creating programs tailored to individual student needs. A total of 108 individuals participated in the study, randomly selected using a simple random sampling technique. The research approach was quantitative. A combination of descriptive data analysis and inferential statistical analysis was used to analyze data collected through observation, questionnaires, and documentation. Having a positive self-concept, acting independently in making judgments, believing in one's talents, and having the courage to share opinions are all signs of self-confidence. Meanwhile, indicators of public speaking competence are ethos, pathos, and logos communication styles. In the Office Administration Education Study Program, Department of Administrative Science, self-confidence has a positive and significant influence on students' public speaking skills (46.3%), while the remaining 54.7% is influenced by other variables not explained in this study